Association among biomarkers, phenotypes, and motor milestones in Chinese patients with 5q spinal muscular atrophy types 1–3 - Ouyang, Shijia; Peng, Xiaoyin; Huang, Wenchen; Bai, Jinli; Wang, Hong; Jin, Yuwei; Jiao, Hui; Wei, Maoti; Ge, Xiushan; Song, Fang; Qu, Yujin (Frontiers in Neurology, 2024)
Background Biomarkers can be used to assess the severity of spinal muscular atrophy (5q SMA; SMA). Despite their potential, the relationship between biomarkers and clinical outcomes in SMA remains underexplored. This study aimed to assess the association among biomarkers, phenotypes, and motor milestones in Chinese patients diagnosed with SMA. Methods We collected retrospective clinical and follow-up data of disease-modifying therapy (DMT)-naïve patients with SMA at our center from 2019 to 2021. Four biomarkers were included: survival motor neuron 2 (SMN2) copies, neuronal apoptosis inhibitory protein (NAIP) copies, full-length SMN2 (fl-SMN2), and F-actin bundling protein plastin 3 (PLS3) transcript levels. Data were analyzed and stratified according to SMA subtype. Results Of the 123 patients, 30 were diagnosed with Type 1 (24.3%), 56 with Type 2 (45.5%), and 37 with Type 3 (30.1%). The mortality rate for Type 1 was 50%, with median survival times of 2 and 8 months for types 1a and 1b, respectively. All four biomarkers were correlated with disease severity. Notably, fl-SMN2 transcript levels increased with SMN2 copies and were higher in Type 2b than those in Type 2a (p = 0.028). Motor milestone deterioration was correlated with SMN2 copies, NAIP copies, and fl-SMN2 levels, while PLS3 levels were correlated with standing and walking function. Discussion Our findings suggest that SMN2 copies contribute to survival and that fl-SMN2 may serve as a valuable biomarker for phenotypic variability in SMA Type 2 subtypes. These insights can guide future research and clinical management of SMA.